A growth and trade oriented model for the Surinamese economy - Birchwood, Anthony (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Constructs a macroeconomic model for Suriname in order to provide a quantitative framework that can be useful for simulation of growth through the analysis of controllable alternative scenarios.